Hate crime in Turkey implications of collective action, media representations and policy making - Göktan, Deniz Ünan (Cambridge Scholars Publishing, 2017)
This book examines how hate crime, as a contemporary legal concept, is introduced and represented in Turkish public discourse. The study addresses questions of how effective the hate crime debate in Turkey has been in identifying bias-motivated violent incidents and how social institutions perceive hate crimes and influence the related debates instigated by social movement actors.First of all, the study explores the movement against hate crime in Turkey, and argues that hate crime has operated as an umbrella term, diverting distinct identity movements into dialogue and collaboration, but has a.